Dialog hutan Jawa : mengurai makna filosofis PHBM - Adam, Sugayo Jawama, 1964-; Raharjo, Imam Fuji. (Yogyakarta : Pustaka Pelajar, 2007)
Illegal logging in Java.
Mode of access: Internet.
Keywords: Logging -- Corrupt practices -- Indonesia -- Java; Deforestation -- Indonesia -- Java